Novel markers of COVID-19 mortality-A comparative study with patients of acute coronary syndrome - Yash Paul Sharma; Atit A. Gawalkar; Akash Batta; Yamasandi Siddegowda Shrimanth; Pruthvi C. Revaiah; Pragya Karki; Vikas Chaudhary; Ganesh Kasinadhuni; Krishna Santosh; Dinakar Bootla; Sanjeev Kumar; Nitin Kumar J Patel; et al. (Journal of Family Medicine and Primary Care)
Background: COVID-19 can cause severe pneumonia that can progress to multiple organ failure. It is believed that dysregulation of inflammation and cytokine storm, contributes to severe COVID-19. As inflammatory mediators play an important role in the pathogenesis of the severe disease, inflammatory markers like fever, leucocytosis, and C-reactive protein are known to predict severe disease. Various other biomarkers have been known to have prognostic value in patients with COVID-19 infection. Inflammation, both local and systemic plays an important role in the pathogenesis of acute coronary syndrome (ACS). Thus in this study, we aimed to compare and describe the various biomarkers, and mortality between patients admitted with COVID-19 infection and ACS patients without COVID-19 infection. Methods: In a retrospective observational case-control study, a total of 108 patients admitted to our hospital during the month of May 2021 with COVID-19 were enrolled. Patients of the acute coronary syndrome (tested negative for COVID-19 infection) admitted during the same month were enrolled (including both the intensive care unit and ward) as controls. Results: The median age of patients with COVID was significantly lower than that of patients with acute coronary syndrome [49 years (IQR, 36-62 years) and 60 years (IQR, 52-66 years)]. Left ventricular ejection fraction was significantly higher among patients with COVID infection (58.5 ± 6.3% versus 36.9 ± 9.3%). The total leukocyte count was significantly higher among patients with COVID-19 compared to those with acute coronary syndrome [13200 per microliter (8625-17500) vs 9800 per microliter (8150-12150), P < 0.001]. The blood urea level was significantly higher among patients with COVID infection [52.5 (IQR, 34.7-81.5) versus 20 (IQR, 16-31)]. Levels of C-reactive protein were significantly higher among patients with COVID [39 (IQR, 7.7-100) versus 2 (1.4-3.5)]. The mortality of patients hospitalized with COVID was 4 times higher than those with acute coronary syndrome [25.9% (28) versus 6.1% (6)]. Survivors of COVID-19 had higher hemoglobin levels than those who did not [12.5 g/dLvs 11.5 g/dL, P = 0.03]. Conclusions: Elevated total leukocyte counts reflect underlying secondary bacterial infection among patients with COVID-19 and help initiate appropriate antibiotics. Depletion of intravascular volume reflected by an increased urea/creatinine ratio increases the risk of mortality and warrants aggressive measures of rehydration and albumin infusion.